1995
DOI: 10.1021/jm00013a003
|View full text |Cite
|
Sign up to set email alerts
|

The role of charge in polyamine analog recognition

Abstract: A series of analogues and homologues of N1,N12-diethylspermine (DESPM) was synthesized, and their biological properties were evaluated. These tetraamines include a simple linear analogue of DESPM, N1,N12-bis(2,2,2-trifluoroethyl)spermine (FDESPM), the cyclic analogues of DESPM, N,N'-bis(4-piperidinylmethyl)-1,4-diaminobutane [PIP(4,4,4)] and N,N'-bis[2-(4-piperidinyl)ethyl]-1,4-diaminobutane [PIP(5,4,5)], and their aromatic counterparts, N,N'-bis-(4-pyridylmethyl)-1,4-diaminobutane [PYR(4,4,4)] and N,N'-bis[2-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
106
1
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 72 publications
(112 citation statements)
references
References 7 publications
(14 reference statements)
4
106
1
1
Order By: Relevance
“…[131] used the intermediate 57 to obtain the SPD derivatives 51 and 58 whereas Bergeron et al [58,133] used the intermediates 59 and 60 to obtain the PA derivatives 51 and 61 and the SPM analogue 62 ( Figure 13). The Boc groups were delivered using the reagents Boc 2 O or Boc-ON, whereas the Bn and Z(NO 2 ) groups were removed by catalytic hydrogenolysis.…”
Section: Methods For the Indirect Functionalization Of The Primary Ammentioning
confidence: 99%
See 3 more Smart Citations
“…[131] used the intermediate 57 to obtain the SPD derivatives 51 and 58 whereas Bergeron et al [58,133] used the intermediates 59 and 60 to obtain the PA derivatives 51 and 61 and the SPM analogue 62 ( Figure 13). The Boc groups were delivered using the reagents Boc 2 O or Boc-ON, whereas the Bn and Z(NO 2 ) groups were removed by catalytic hydrogenolysis.…”
Section: Methods For the Indirect Functionalization Of The Primary Ammentioning
confidence: 99%
“…Weakly charged PA analogues cannot compete with natural PAs for transport through the cell membranes. [58] PAs bearing bulky alkyl substituents on the terminal nitrogen atoms are not efficiently transported, whereas the distance between the nitrogen functions appears to play an important role in their recognition by the PA uptake system. [58,59] Parallel work has been carried out in procaryotic cells.…”
Section: Various Polyamine Conjugatesmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of N-(3-phenylpropyl) substituted spermine analogs have been reported that act as potent inhibitors of TR [146]. It has been suggested that alkyl-and aralkyl-substituted polyamine analogs disrupt polyamine metabolism because the nitrogen pK a values have been altered, leading to reductions in their degree of protonation at physiological pH [21,147,148]. A key advantage to these compounds as antiparasitic agents is that they selectively enter proliferating cells using the trypanosomal polyamine transport system, where they down regulate the biosynthetic enzymes ODC and AdoMet-DC.…”
Section: Inhibitors Of Parasitic Glucose Metabolism and Glycosomal Trmentioning
confidence: 99%